SPEECH ACTS ANALYSIS IN DESMONDâ€™S CONVERSATION IN â€œHACKSAW RIDGEâ€ MOVIE - Paswasari Yuani Kiuk; Imam Ghozali (JELLT (Journal of English Language and Language Teaching), 2018)
The aims of this research are to describe the types and the functions of speech act performed by Desmond in his conversations in Hacksaw Ridge movie. The data sources of the research were taken from the movie script. After collecting the data, the data are selected, reduced and analyzed using Searleâ€™s theory of speech act in Speech Acts Essay in the Philosophy of Language book in 1977. The result of this research shows that there are five types of speech act act in 231 utterances consisting 78 utterances of directive, 165 utterances of representative, 10 utterances of expressive, 12 utterances of commissive and 2 utterances of declarative in the Hacksaw Ridge movie. The functions of speech act are utterances of stating complaining, alerting, claiming, concluding, reporting, affirming, forecasting, insisting, asserting, questioning, ordering, begging, demanding, commanding, requesting, suggesting, promising, offering, refusing, apologizing, blaming, yelling, thanking, liking, praising, mocking, being ashamed, declaring war, and love. It can be concluded that the most kinds of speech act used by the main character is representative act of stating.